Health monitoring before and after independent learning during the pandemic - Handayani, Lisda; Suhartati, Susanti; Irawan, Angga; Zulfadhilah, Muhammad (Ananda - Health & Education Foundation, 2024)
Background: The COVID-19 pandemic significantly impacted educational practices globally, including Indonesia's Merdeka Belajar-Kampus Merdeka (MBKM) program, which emphasizes real-world learning experiences. Health monitoring became a crucial aspect of student safety during MBKM activities, particularly in community settings. This report examines the health protocols implemented by Universitas Sari Mulia during a humanitarian mission in response to the South Kalimantan floods amidst the pandemic. Case presentation: Sari Mulia University deployed 327 students to assist in four sub-districts affected by floods. To prevent the spread of COVID-19, pre-deployment health protocols included rapid antigen testing, which identified five asymptomatic positive cases requiring isolation. After completing the two-month MBKM program, students were tested again, revealing seven additional cases, including one with moderate symptoms, while others were either mild or asymptomatic. Discussion: The university's health monitoring protocols, including pre- and post-deployment testing, isolation, and symptom-based treatments, significantly minimized virus transmission. The importance of early detection and close monitoring of asymptomatic individuals is emphasized, as undetected cases could contribute to community transmission. Additionally, the program highlights the necessity of integrating health education into MBKM activities to ensure students understand preventive health measures. Conclusion: Universitas Sari Mulia successfully implemented comprehensive health monitoring during its MBKM program, protecting both students and the communities they served. This case underscores the need for ongoing health vigilance, education, and institutional collaboration to safely conduct off-campus learning during the pandemic. These practices serve as a model for future MBKM programs across Indonesia.